Preparation method and application of zinc-bromine static battery positive electrode material

By introducing pyridine nitrogen and fixed cyclodextrin on multi-walled carbon nanotubes, a positive electrode material enriched with Brˉ and Br3ˉ structures and efficient catalytic sites was formed, which solved the problems of large charging and polarization and self-discharge of zinc-brominated static batteries, and significantly improved the energy efficiency and storage stability of the battery.

CN119764469AActive Publication Date: 2025-04-04GUANGXI UNIV FOR NATITIES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411995784.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Zinc-brominated static batteries have a large charge polarization during charging, and are prone to self-discharge during storage, affecting energy efficiency and storage stability.

Method used

Multi-walled carbon nanotubes are used as substrates, and the carboxylic group is connected by introducing pyridine nitrogen and surface activation, and cyclodextrin is fixed through esterification reaction to form a positive electrode material that is enriched with Brˉ and Br3ˉ structures and efficient catalytic sites.

Benefits of technology

It effectively reduces the charging polarization of zinc-brominated static batteries, significantly improves the self-discharge performance, and improves the energy efficiency and storage stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764469A_ABST
    Figure CN119764469A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a zinc-bromine static battery positive electrode material, and relates to the technical field of battery energy storage. The preparation method comprises the following steps: (1) calcining a multi-walled carbon nanotube in an ammonia atmosphere, and naturally cooling to obtain a nitrogen-doped multi-walled carbon nanotube; (2) adding a strong oxidant into the nitrogen-doped multi-walled carbon nanotube, carrying out ultrasonic dispersion, reflux condensation and filtration, then washing the nitrogen-doped multi-walled carbon nanotube with a sodium hydroxide solution until the nitrogen-doped multi-walled carbon nanotube is neutral, then washing the nitrogen-doped multi-walled carbon nanotube with deionized water, and drying the nitrogen-doped multi-walled carbon nanotube to obtain a carboxylated nitrogen-doped multi-walled carbon nanotube; and (3) adding cyclodextrin into the carboxylated nitrogen-doped multi-walled carbon nanotube, carrying out ultrasonic dispersion, stirring, filtering, washing with ultrapure water, and drying to obtain a cyclodextrin-nitrogen-doped multi-walled carbon nanotube, namely the positive electrode material. The positive electrode material prepared by the invention has a structure enriched with Br <-> and Br < 3-> and efficient catalytic sites, and effectively solves the problems of large charge polarization and self-discharge of a zinc-bromine static battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery energy storage, and in particular to a preparation method and application of a zinc-bromine static battery positive electrode material. Background Art

[0002] Based on Zn 2+ Zinc-bromine flow batteries, which react with the ions of Zn / Zn (negative electrode) and Br2 / Brˉ (positive electrode), have always been strong competitors in the large-scale energy storage market due to their high safety and theoretical energy density. On this basis, zinc-bromine static batteries that eliminate expensive ion exchange membranes and circulating separation storage systems have attracted widespread attention and strong interest in the market with their breakthrough cost advantages. Such batteries generally use carbon-based materials as positive electrodes and ZnBr2 aqueous solutions as electrolytes.

[0003] However, zinc-bromine static batteries face huge challenges in practical applications: during the charging process, the electrochemical oxidation reaction of Brˉ on carbon-based materials is slow, resulting in increased charging polarization and reduced energy efficiency of the system; during storage, Brˉ reacts with the positive electrode charging product Br2 to form Br3ˉ, which is easily soluble in water, and diffuses to the negative electrode driven by the concentration gradient, reacts with Zn, and causes severe self-discharge behavior. Therefore, introducing a structure that can enrich Brˉ and Br3ˉ and a high-efficiency catalytic site into the positive electrode of the battery to solve the large charging polarization and self-discharge behavior of zinc-bromine static batteries is of great significance to promote the practical application of zinc-bromine static batteries.

[0004] In the prior art, patent CN 116742092 A discloses a homogeneous electrolyte for the positive electrode of zinc-bromine flow battery. The patent uses cyclodextrin derivatives (methylated cyclodextrin, hydroxyethyl cyclodextrin, hydroxypropyl cyclodextrin, carboxymethyl cyclodextrin, sulfate cyclodextrin, sulfonate cyclodextrin, phosphate cyclodextrin) as bromine complexes to obtain zinc-bromine flow battery with excellent CE, VE and EE. Patent CN 118431529 A discloses the application of a bromine capture agent based on supramolecular assembly in zinc-bromine flow battery. The patent uses cyclodextrin and its derivatives as bromine capture agents to effectively improve the coulombic efficiency of the battery. The above patents all use the technology of dissolving cyclodextrin into the electrolyte to improve the performance of zinc-bromine flow battery. In zinc-bromine static battery, if the same technology is used, cyclodextrin complexed with Br3ˉ will still diffuse to the negative electrode driven by the concentration gradient, resulting in self-discharge. Therefore, it is necessary to further improve the method of enriching Brˉ and Br3ˉ for the practical application of zinc-bromine static batteries. Summary of the invention

[0005] In view of the above shortcomings, the present invention provides a preparation method and application of a positive electrode material for a zinc-bromine static battery. The positive electrode material has a structure enriched with Brˉ and Br3ˉ and a high-efficiency catalytic site, which effectively solves the problems of large charging polarization and self-discharge of the zinc-bromine static battery. The specific technical scheme is as follows:

[0006] A method for preparing a positive electrode material for a zinc-bromine static battery comprises the following steps:

[0007] (1) calcining multi-walled carbon nanotubes (CNTs) in an ammonia atmosphere for 6-10 hours at a calcination temperature of 300-450° C., and cooling naturally to obtain nitrogen-doped multi-walled carbon nanotubes (NCNTs);

[0008] (2) adding a strong oxidant to the NCNTs, ultrasonically dispersing for 30-40 min, condensing and refluxing at a speed of 1000-1200 rpm and a temperature of 40-80° C. for 6-12 h, filtering, then washing with a sodium hydroxide solution until neutral, then washing with deionized water, and drying at 70-85° C. for 8-10 h to obtain carboxylated nitrogen-doped multi-walled carbon nanotubes (NCNTs-COOH);

[0009] (3) Add cyclodextrin (CD) to the NCNTs-COOH, ultrasonically disperse for 30-60 minutes, stir, filter, wash with ultrapure water, and dry at 60-80° C. for 8-12 hours to obtain cyclodextrin-nitrogen-doped multi-walled carbon nanotubes (CD-NCNTs), which is the positive electrode material.

[0010] Furthermore, in step (1), before the calcination treatment, ammonia is introduced for 15-30 minutes, the gas flow rate of ammonia during the calcination process is 20-25 mL / min, and argon is introduced after the calcination to remove residual ammonia, and the argon introduction time is not less than 15 minutes.

[0011] Furthermore, in step (2), the oxidant is potassium permanganate, concentrated nitric acid, or a mixture of concentrated sulfuric acid and concentrated nitric acid.

[0012] Furthermore, in the mixture of concentrated sulfuric acid and concentrated nitric acid, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3-4:1.

[0013] Furthermore, in step (2), the concentration of the sodium hydroxide solution is 0.1-0.5 mol / L.

[0014] Furthermore, in step (2), the cyclodextrin is one or more of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, hydroxypropyl-α-cyclodextrin, hydroxyethyl-β-cyclodextrin and hydroxypropyl-γ-cyclodextrin.

[0015] Furthermore, in step (3), the stirring is stirring at room temperature. When stirring at room temperature, the preparation method of CD-NCNTs is: 0.2-0.5g of the NCNTs-COOH and 20-40mL of saturated CD solution are placed in a 100mL flask, ultrasonically dispersed for 30-60min, stirred at room temperature for 8-10h, filtered, washed with ultrapure water for 5-7 times, and dried at 60-80°C for 8-12h to obtain CD-NCNTs.

[0016] Furthermore, in step (3), the stirring is heating stirring. During heating stirring, the preparation method of CD-NCNTs is as follows: 0.2-0.5g of the NCNTs-COOH and 10 times its mass of CD powder are placed in a 100mL flask, 30-40mL of water are added, ultrasonic dispersion is performed for 30-60min, heating to 60-80°C and stirring for 18-20h, filtering, washing with ultrapure water for 5-7 times, and drying at 60-80°C for 8-12h to obtain CD-NCNTs.

[0017] The present invention also provides a method for preparing a positive electrode of a battery, which is prepared by using the above-mentioned positive electrode material. The specific preparation method is: first, CD-NCNTs, XC-72 conductive carbon, and polytetrafluoroethylene are uniformly mixed according to a mass ratio of 90:5:5, and isopropanol is added to prepare the slurry. Then, the slurry is pressed into a thin sheet by a stainless steel rolling machine and vacuum dried at 120°C. Finally, the thin sheet is cut into a suitable size to obtain the positive electrode of the battery.

[0018] The present invention also provides a zinc-bromine static battery, which consists of a positive electrode, a negative electrode, a diaphragm and an electrolyte, wherein the positive electrode is the battery positive electrode prepared by the above method, the negative electrode is a commercially available zinc foil, the diaphragm is a commercially available microporous diaphragm, and the electrolyte formula is a 1-3 mol / L ZnBr2 aqueous solution.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The present invention proposes for the first time a zinc-bromine static battery cathode material, which has a structure enriched with Brˉ and Br3ˉ, and a highly efficient catalytic site. Specifically, pyridinic nitrogen is first introduced into multi-walled carbon nanotubes, followed by surface activation and access to carboxyl groups, and finally, esterification reaction occurs between carboxyl groups and hydroxyl groups in cyclodextrin molecules to fix cyclodextrin on nitrogen-doped multi-walled carbon nanotubes, thereby obtaining cyclodextrin-nitrogen-doped multi-walled carbon nanotubes.

[0021] 2. The zinc-bromine static battery positive electrode material prepared by the present invention introduces pyridine nitrogen as an efficient catalytic site, and fixes cyclodextrin as a structure for enriching Brˉ and Br3ˉ, which effectively solves the problems of large charging polarization and self-discharge of zinc-bromine static batteries. Specifically, during the charging process, the fixed cyclodextrin structural unit in the material and the introduced pyridine nitrogen play the role of enriching Brˉ and catalyzing Brˉ oxidation, respectively, and relay to improve the mass transfer capacity and reaction activity, promote the rapid progress of electrochemical oxidation reaction, and thus effectively reduce the charging polarization; during the storage process, the fixed cyclodextrin structural unit in the material efficiently enriches Br3ˉ, plays the role of a material reserve, inhibits the diffusion behavior of Br3ˉ, that is, hinders the diffusion of positive electrode charging products to the negative electrode, thereby significantly improving the self-discharge performance.

[0022] 3. The present invention calcines the multi-walled carbon nanotubes in an ammonia atmosphere to generate pyridinic nitrogen. The introduction of pyridinic nitrogen into the multi-walled carbon nanotubes can make the material have efficient catalytic sites.

[0023] 4. In the present invention, a strong oxidant is added during the reaction process to oxidize the NCNTs, so that after the surface of the NCNTs is activated, oxygen-containing groups such as carboxyl groups are introduced to provide reaction sites for the subsequent connection and fixation of cyclodextrin. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below.

[0025] Figure 1 XPS data of NCNTs prepared in the present invention;

[0026] Figure 2 Infrared spectra of the materials prepared in the present invention: (A) NCNTs, (B) NCNTs-COOH, (C) β-CD, (D) β-CD-NCNTs;

[0027] Figure 3 SEM images of the materials prepared in the present invention: (A) NCNTs, (B) NCNTs-COOH, (C) β-CD-NCNTs. DETAILED DESCRIPTION

[0028] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.

[0029] The CDs used in the following examples and comparative examples were purchased from Aladdin Chemical Reagent Company, and the CNTs were purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences.

[0030] Example 1

[0031] The present embodiment provides a method for preparing a positive electrode material for a zinc-bromine static battery, comprising the following steps:

[0032] (1) Preparation of NCNTs: 0.5 g of CNTs powder was placed in a 30 mL magnetic boat, which was placed in a tube furnace. Ammonia was introduced for 15 min to ensure that the reaction environment was filled with ammonia. The material was heated to 300 °C at a heating rate of 15 °C / min and the target temperature was maintained for 8 h. The gas flow rate of ammonia during the calcination process was 20 mL / min. After the insulation was completed, argon was introduced to remove excess ammonia. The material was naturally cooled to room temperature to obtain NCNTs.

[0033] (2) Preparation of NCNTs-COOH: 1 g of NCNTs powder was placed in a 150 mL round-bottom flask, 100 mL of concentrated nitric acid solution was added, and the mixture was dispersed under ultrasonic conditions for 30 min. The dispersed solution was condensed and refluxed at 80 °C and 1200 rpm for 6 h. After the reaction, the product was filtered and neutralized with 0.1 mol / L sodium hydroxide solution to neutrality. The product was then washed with deionized water for 5 times to remove residual acidic substances. The washed product was dried at 80 °C for 8 h to obtain NCNTs-COOH.

[0034] (3) Preparation of β-CD-NCNTs: 0.5 g NCNTs-COOH and 30 mL saturated β-cyclodextrin (β-CD) solution were placed in a 100 mL flask and ultrasonically treated for 30 min to ensure uniform dispersion. The mixture was stirred overnight at room temperature. After stopping stirring, the product was filtered and washed with ultrapure water to remove excess β-CD. The final product was dried at 80 °C for 8 h to obtain β-CD-NCNTs.

[0035] The XPS data of NCNTs prepared in this example are as follows Figure 1 As shown, a nitrogen characteristic peak appears in the material, with the peak value located at 398.3 eV, indicating that pyridinic nitrogen is successfully introduced into CNTs to produce NCNTs.

[0036] The infrared spectrum of the material prepared in this example is as follows Figure 2 As shown in the figure, after oxidation treatment, NCNTs (substance A) has a 1 The -CO- bond appears at the NCNTs surface, indicating that the carboxyl group (-COOH) is successfully connected to the NCNTs surface (substance B). In the subsequent esterification reaction of cyclodextrin, the infrared spectrum of the material is 1600cm- 1 (-C=O-), 1750cmˉ 1 (-C=C-) and a signal at 1100cmˉ 1The positive shift of -CO- vibration at β-CD indicates that the carboxyl group undergoes esterification reaction with β-CD to form β-CD-NCNTs (substance D).

[0037] The SEM image of the material prepared in this example is as follows Figure 3 As shown in the figure, compared with NCNTs (Figure A), after surface activation and access to carboxyl groups, the obtained NCNTs-COOH did not show obvious changes (Figure B). Further esterification reaction occurred, and the β-CD-NCNTs obtained by fixing β-CD showed adhesion (Figure C), which may be due to the rich hydrogen bonding of β-CD inducing the aggregation of the material.

[0038] Example 2

[0039] The present embodiment provides a method for preparing a positive electrode material for a zinc-bromine static battery, comprising the following steps:

[0040] (1) Preparation of NCNTs: 1 g of CNTs powder was placed in a 30 mL magnetic boat, which was placed in a tube furnace. Ammonia was introduced for 15 min to ensure that the reaction environment was filled with ammonia. The material was heated to 350 °C at a heating rate of 20 °C / min and the target temperature was maintained for 8 h. The gas flow rate of ammonia during the calcination process was 25 mL / min. After the insulation was completed, argon was introduced to remove excess ammonia. The material was naturally cooled to room temperature to obtain NCNTs.

[0041] (2) Preparation of NCNTs-COOH: 1 g of NCNTs powder was placed in a 150 mL round-bottom flask, 100 mL of potassium permanganate solution was added, and the mixture was dispersed under ultrasonic conditions for 40 min; the mixture was condensed and refluxed at 80 °C and 1200 rpm for 8 h; the product was filtered and washed with 0.1 mol / L sodium hydroxide solution until neutral, and then washed thoroughly with a large amount of deionized water. The washed product was dried at 80 °C for 8 h to obtain NCNTs-COOH.

[0042] (3) Preparation of β-CD-NCNTs: 0.5 g NCNTs-COOH and 30 mL saturated β-CD solution were placed in a 100 mL flask and ultrasonically treated for 30 min to ensure uniform dispersion. The mixture was stirred overnight at room temperature. After stopping stirring, the product was filtered and washed with ultrapure water to remove excess β-CD. The final product was dried at 80 °C for 8 h to obtain β-CD-NCNTs.

[0043] Example 3

[0044] The present embodiment provides a method for preparing a positive electrode material for a zinc-bromine static battery, comprising the following steps:

[0045] (1) Preparation of NCNTs: 1 g of CNTs powder was placed in a 30 mL magnetic boat, which was placed in a tube furnace. Ammonia was introduced for 20 min to ensure that the reaction environment was filled with ammonia. The material was heated to 400 °C at a heating rate of 20 °C / min and the target temperature was maintained for 10 h. The gas flow rate of ammonia during the calcination process was 20 mL / min. After the insulation was completed, argon was introduced to remove excess ammonia. The material was naturally cooled to room temperature to obtain NCNTs.

[0046] (2) Preparation of NCNTs-COOH: 1 g of NCNTs powder was placed in a 150 mL round-bottom flask, and a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a ratio of 3:1 was added. The mixture was dispersed under ultrasonic conditions for 30 min, and condensed and refluxed at 80 °C and 1200 rpm for 6 h. After filtering the product, it was washed with 0.1 mol / L sodium hydroxide solution until neutral, and then washed thoroughly with a large amount of deionized water. The washed product was dried at 80 °C for 8 h to obtain NCNTs-COOH.

[0047] (3) Preparation of β-CD-NCNTs: 0.5 g NCNTs-COOH and 30 mL saturated β-CD solution were placed in a 100 mL flask and ultrasonically treated for 30 min to ensure uniform dispersion. The mixture was stirred overnight at room temperature. After stopping stirring, the product was filtered and washed with ultrapure water to remove excess β-CD. The final product was dried at 80 °C for 8 h to obtain β-CD-NCNTs.

[0048] Example 4

[0049] The present embodiment provides a method for preparing a positive electrode material for a zinc-bromine static battery, comprising the following steps:

[0050] (1) Preparation of NCNTs: 0.5 g of CNTs powder was placed in a 30 mL magnetic boat, which was placed in a tube furnace. Ammonia was introduced for 15 min to ensure that the reaction environment was filled with ammonia. The material was heated to 300 °C at a heating rate of 15 °C / min and the target temperature was maintained for 8 h. The gas flow rate of ammonia during the calcination process was 20 mL / min. After the insulation was completed, argon was introduced to remove excess ammonia. The material was naturally cooled to room temperature to obtain NCNTs.

[0051] (2) Preparation of NCNTs-COOH: 1 g of NCNTs powder was placed in a 150 mL round-bottom flask, 100 mL of concentrated nitric acid solution was added, and the mixture was dispersed under ultrasonic conditions for 30 min. The dispersed solution was condensed and refluxed at 80 °C and 1200 rpm for 6 h. After the reaction, the product was filtered and neutralized with 0.1 mol / L sodium hydroxide solution to neutrality. The product was then washed with deionized water for 5 times to remove residual acidic substances. The washed product was dried at 80 °C for 8 h to obtain NCNTs-COOH.

[0052] (3) Preparation of β-CD-NCNTs: 0.2 g NCNTs-COOH and 1 g β-CD powder were placed in a 100 mL flask, and 30 mL deionized water was added. Ultrasonic dispersion was performed for 30 min to ensure uniform mixing. The mixture was heated to 60 °C and stirred at this temperature for 20 h to promote the esterification reaction. After stopping stirring, the product was filtered and washed with ultrapure water. The product was washed with ultrapure water for 7 times to remove excess β-CD. The washed product was dried at 80 °C for 8 h to obtain β-CD-NCNTs.

[0053] Example 5

[0054] This embodiment is a method for preparing a positive electrode material for a zinc-bromine static battery. Except that the ultrasonic dispersion time in step (3) is 60 minutes, the other steps are the same as those in Example 4.

[0055] Example 6

[0056] This embodiment is a method for preparing a positive electrode material for a zinc-bromine static battery. Except that the stirring time in step (3) is 20 hours, the other steps are the same as those in Example 4.

[0057] Example 7

[0058] The present embodiment is a method for preparing a positive electrode material for a zinc-bromine static battery. Steps (1) and (2) are the same as those in Example 1. Step (3) is prepared using α-cyclodextrin (α-CD), specifically as follows: 0.2 g NCNTs-COOH and 2 g α-CD powder are placed in a 100 mL flask, an appropriate amount of deionized water is added, and ultrasonic treatment is performed for 30 min to ensure uniform mixing. The mixture is heated to 60 ° C and stirred under reflux for 20 h to promote the esterification reaction to proceed fully. After stopping stirring, filter, wash with ultrapure water, and wash 5 times with ultrapure water to remove excess α-CD. Dry at 80 ° C for 8 h to obtain α-CD-NCNTs.

[0059] Example 8

[0060] The present embodiment is a method for preparing a positive electrode material for a zinc-bromine static battery. Steps (1) and (2) are the same as those in Example 1. Step (3) is prepared using γ-cyclodextrin (γ-CD), specifically as follows: 0.2 g NCNTs-COOH and 2 g γ-CD powder are placed in a 100 mL flask, an appropriate amount of deionized water is added, and ultrasonic treatment is performed for 30 min to ensure uniform mixing. The mixture is heated to 60° C. and stirred under reflux for 20 h to promote the esterification reaction to proceed fully. After stopping stirring, filter, wash with ultrapure water, and wash 5 times with ultrapure water to remove excess γ-CD. Dry at 80° C. for 8 h to obtain γ-CD-NCNTs.

[0061] Example 9

[0062] This embodiment is a method for preparing a positive electrode material for a zinc-bromine static battery. Steps (1) and (2) are the same as those in Example 1. Step (3) is prepared using hydroxyethyl-β-cyclodextrin (HE-β-CD), specifically as follows: 0.2 g NCNTs-COOH and 2 g HE-β-CD powder are placed in a 100 mL flask, an appropriate amount of deionized water is added, and ultrasonic treatment is performed for 30 min. The mixture is heated to 60° C., and stirred under hot reflux for 15 h. After stopping stirring, the mixture is filtered and washed with ultrapure water for 5 times to remove excess HE-β-CD. The mixture is dried at 80° C. for 8 h to obtain a HE-β-CD-NCNTs material.

[0063] Example 10

[0064] The present embodiment provides a method for preparing a positive electrode material for a zinc-bromine static battery. Step (1) and step (2) are the same as those in Example 1. Step (3) is prepared using hydroxypropyl-α-cyclodextrin (HP-α-CD), specifically as follows: 0.2 g NCNTs-COOH and 1 g HP-α-CD powder are placed in a 100 mL flask, an appropriate amount of deionized water is added, and ultrasonic treatment is performed for 20 min. The mixture is heated to 50° C. and stirred for 12 h. After stopping stirring, the mixture is filtered and washed with ultrapure water. The mixture is washed with ultrapure water for 5 times to remove excess HP-α-CD, and the mixture is dried at 80° C. for 8 h to obtain HP-α-CD-NCNTs material.

[0065] Embodiment 11

[0066] The present embodiment provides a method for preparing a positive electrode material for a zinc-bromine static battery. Step (1) and step (2) are the same as those in Example 1. Step (3) is prepared using hydroxypropyl-γ-cyclodextrin (HP-γ-CD), specifically as follows: 0.2 g NCNTs-COOH and 1 g HP-γ-CD powder are placed in a 100 mL flask, an appropriate amount of deionized water is added, and ultrasonic treatment is performed for 30 min. The mixture is heated to 65° C. and stirred for 18 h to promote the esterification reaction. After stopping stirring, the mixture is filtered and washed with ultrapure water for 7 times to remove excess HP-γ-CD, and dried at 80° C. for 8 h to obtain HP-γ-CD-NCNTs material.

[0067] Preparation of battery positive electrode: The CD-NCNTs positive electrode material synthesized in each embodiment is used for preparation. The specific preparation method is: first, CD-NCNTs, XC-72 conductive carbon, and polytetrafluoroethylene are evenly mixed in a mass ratio of 90:5:5, and isopropanol is added to prepare the slurry. Then, the slurry is pressed into a thin sheet by a stainless steel rolling machine and vacuum dried at 120°C. Finally, the thin sheet is cut into a suitable size to obtain the battery positive electrode.

[0068] Preparation of zinc-bromine static battery: The zinc-bromine static battery in each embodiment is composed of a positive electrode, a negative electrode, a diaphragm and an electrolyte, wherein the positive electrode is the battery positive electrode prepared by the above method, the negative electrode is a commercially available zinc foil, the diaphragm is a commercially available microporous diaphragm, and the electrolyte formula is a 2 mol / L ZnBr2 aqueous solution.

[0069] Comparative Example 1

[0070] The positive electrode preparation method of this comparative example is: first, CNTs, XC-72 conductive carbon, and polytetrafluoroethylene are uniformly mixed in a mass ratio of 90:5:5, isopropyl alcohol is added to prepare the slurry, and then the slurry is pressed into a thin sheet by a stainless steel rolling machine and vacuum dried at 120° C. Finally, the thin sheet is cut into a suitable size to obtain the battery positive electrode.

[0071] The zinc-bromine static battery of this comparative example consists of a positive electrode, a negative electrode, a diaphragm and an electrolyte, wherein the positive electrode is the battery positive electrode prepared by the above method, the negative electrode is a commercially available zinc foil, the diaphragm is a commercially available microporous diaphragm, and the electrolyte formula is a 2 mol / L ZnBr2 aqueous solution.

[0072] Comparative Example 2

[0073] The positive electrode preparation method of this comparative example is the same as that of comparative example 1.

[0074] The zinc-bromine static battery of this comparative example consists of a positive electrode, a negative electrode, a diaphragm and an electrolyte, wherein the positive electrode is the battery positive electrode prepared by the above method, the negative electrode is a commercially available zinc foil, the diaphragm is a commercially available microporous diaphragm, and the electrolyte formula is 2 mol / L ZnBr2 aqueous solution + 0.2 mol / L HP-α-CD.

[0075] Comparative Example 3

[0076] The positive electrode preparation method of this comparative example is the same as that of comparative example 1.

[0077] The zinc-bromine static battery of this comparative example consists of a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode is the battery positive electrode prepared by the above method, the negative electrode is a commercially available zinc foil, the separator is a commercially available microporous separator, and the electrolyte formula is 2 mol / L ZnBr2 aqueous solution + 0.2 mol / L HE-β-CD.

[0078] Performance Test:

[0079] (1) The zinc-bromine static batteries of each embodiment and each comparative example were subjected to electrochemical tests to examine the charging polarization and self-discharge performance. The experimental conditions were:

[0080] The test temperature is 25℃; the current density of charge and discharge is the same, and two current densities are selected: 10 and 40mA / cm 2 The charge cut-off voltage is 1.8V, and the discharge cut-off voltage is 0.6V. The severity of the battery charge polarization is evaluated by the voltage difference between the charge platform and the discharge platform. For the investigation of self-discharge performance, the discharge energy retention rate of the battery is compared after charging to the cut-off voltage and standing for 4 days.

[0081] (2) The battery performance test results are shown in Table 1:

[0082] Table 1 Battery performance test results of the embodiment and the comparative example

[0083]

[0084]

[0085] (3) The results show that the difference between the embodiment and comparative example 1 is that the positive electrode of the embodiment adopts the CD-NCNTs prepared by the present invention, while comparative example 1 adopts CNTs, and the electrolyte is 2 mol / L ZnBr2 aqueous solution. At different current densities, the charge-discharge voltage difference of the embodiment is smaller than that of comparative example 1, and the static discharge energy retention rate is much greater than that of comparative example 1, indicating that the embodiment has a smaller charge polarization and lower self-discharge than comparative example 1. This means that by introducing pyridine nitrogen as an efficient catalytic site and fixing cyclodextrin as a structure enriched with Brˉ and Br3ˉ, the problems of large charge polarization and self-discharge of zinc-bromine static batteries are effectively solved.

[0086] In addition, in order to evaluate the effect of the technology of dissolving cyclodextrin into the electrolyte adopted by patents CN 116742092 A and CN 118431529 A on the self-discharge performance of zinc-bromine static batteries, we prepared comparative examples 2 and 3. The results of the static discharge energy retention rate of the battery showed that the technology of dissolving cyclodextrin into the electrolyte could not improve the self-discharge performance of zinc-bromine static batteries.

[0087] In summary, the present invention first introduces pyridine nitrogen on multi-walled carbon nanotubes, then performs surface activation, connects carboxyl groups, and finally esterifies carboxyl groups with hydroxyl groups in cyclodextrin molecules to fix cyclodextrin on nitrogen-doped multi-walled carbon nanotubes, thereby obtaining a positive electrode material (CD-NCNTs) with a structure enriched with Brˉ and Br3ˉ and a highly efficient catalytic site, which is used to make a positive electrode of a zinc-bromine static battery. During the charging process, the fixed cyclodextrin structural unit in the material and the introduced pyridine nitrogen play the role of enriching Brˉ and catalyzing Brˉ oxidation, respectively, and relay to improve the mass transfer capacity and reaction activity, promote the rapid progress of the electrochemical oxidation reaction, and thus effectively reduce the charging polarization; during the storage process, the fixed cyclodextrin structural unit in the material efficiently enriches Br3ˉ, plays the role of a material reserve, inhibits the diffusion behavior of Br3ˉ, that is, hinders the diffusion of the positive electrode charging product to the negative electrode, thereby significantly improving the self-discharge performance, and effectively solving the problem of large charging polarization and self-discharge of zinc-bromine static batteries.

[0088] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A method for preparing a positive electrode material for a zinc-bromine static battery, characterized in that: The following steps are involved: (1) calcining the multi-walled carbon nanotubes in an ammonia atmosphere for 6-10 hours at a calcination temperature of 300-450° C., and cooling naturally to obtain nitrogen-doped multi-walled carbon nanotubes; (2) adding a strong oxidant to the nitrogen-doped multi-walled carbon nanotubes, ultrasonically dispersing for 30-40 min, condensing and refluxing at a speed of 1000-1200 rpm and a temperature of 40-80° C. for 6-12 h, filtering, then washing with a sodium hydroxide solution until neutral, then washing with deionized water, and drying at 70-85° C. for 8-10 h to obtain carboxylated nitrogen-doped multi-walled carbon nanotubes; (3) Add cyclodextrin to the carboxylated nitrogen-doped multi-walled carbon nanotubes, ultrasonically disperse for 30-60 minutes, stir, filter, wash with ultrapure water, and dry at 60-80° C. for 8-12 hours to obtain cyclodextrin-nitrogen-doped multi-walled carbon nanotubes, which are the positive electrode material.

2. The method for preparing a positive electrode material for a zinc-bromine static battery according to claim 1, characterized in that: In step (1), before the calcination treatment, ammonia is introduced for 15-30 minutes, and the gas flow rate of ammonia during the calcination process is 20-25 mL / min. After the calcination is completed, argon is introduced to remove residual ammonia, and the argon introduction time is not less than 15 minutes.

3. The method for preparing a positive electrode material for a zinc-bromine static battery according to claim 1, characterized in that: In step (2), the oxidant is potassium permanganate, concentrated nitric acid, or a mixture of concentrated sulfuric acid and concentrated nitric acid.

4. The method for preparing a positive electrode material for a zinc-bromine static battery according to claim 3, characterized in that: In the mixture of concentrated sulfuric acid and concentrated nitric acid, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3-4:

1.

5. The method for preparing a positive electrode material for a zinc-bromine static battery according to claim 1, characterized in that: In step (2), the concentration of the sodium hydroxide solution is 0.1-0.5 mol / L.

6. The method for preparing a positive electrode material for a zinc-bromine static battery according to claim 1, characterized in that: In step (2), the cyclodextrin is one or more of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, hydroxypropyl-α-cyclodextrin, hydroxyethyl-β-cyclodextrin and hydroxypropyl-γ-cyclodextrin.

7. The method for preparing a positive electrode material for a zinc-bromine static battery according to claim 1, characterized in that: In step (3), the stirring is stirring at room temperature. When stirring at room temperature, the preparation method of cyclodextrin-nitrogen-doped multi-walled carbon nanotubes is: adding saturated cyclodextrin to the carboxylated nitrogen-doped multi-walled carbon nanotubes, ultrasonically dispersing for 30-60 minutes, stirring at room temperature for 8-10 hours, filtering, washing with ultrapure water, and drying at 60-80°C for 8-12 hours to obtain cyclodextrin-nitrogen-doped multi-walled carbon nanotubes.

8. The method for preparing a positive electrode material for a zinc-bromine static battery according to claim 1, characterized in that: In step (3), the stirring is heating stirring. During heating stirring, the preparation method of cyclodextrin-nitrogen-doped multi-walled carbon nanotubes is as follows: cyclodextrin powder and water are added to the carboxylated nitrogen-doped multi-walled carbon nanotubes, ultrasonically dispersed for 30-60 minutes, heated to 60-80°C and stirred for 18-20 hours, filtered, washed with ultrapure water, and dried at 60-80°C for 8-12 hours to obtain cyclodextrin-nitrogen-doped multi-walled carbon nanotubes.

9. A method for preparing a positive electrode of a battery, characterized in that: The positive electrode material prepared by the method described in any one of claims 1 to 8 is prepared, and the specific preparation method is: first, the cyclodextrin-nitrogen doped multi-walled carbon nanotubes, XC-72 conductive carbon, and polytetrafluoroethylene are evenly mixed in a mass ratio of 90:5:5, and isopropanol is added to prepare the slurry, and then the slurry is pressed into a thin sheet by a stainless steel rolling machine and vacuum dried at 120°C, and finally the thin sheet is cut into a suitable size to obtain the battery positive electrode.

10. A zinc-bromine static battery, characterized in that: The battery adopts the battery positive electrode as claimed in claim 9 as the positive electrode.

Citation Information

Patent Citations

  • Method for grafting carbon nanotubes by using cyclodextrin

    CN102140145A

  • Preparation method and application of Beta-cyclodextrin grafted carbon nano tube adsorbing material

    CN102688752A

  • Preparation method of magnetic carbon tube-molybdenum disulfide nano-enzyme and method for detecting hydrogen peroxide and glucose by using same

    CN109387508A

  • Shuttling-free batteries and preparation method thereof

    WO2024055059A1